Update on animal models of diabetic retinopathy: from molecular approaches to mice and higher mammals - Robinson, Remya (The Company of Biologists Limited, 2012)
Diabetic retinopathy (DR) is the most common microvascular complication of diabetes and one of the major causes of blindness worldwide. The pathogenesis of DR has been investigated using several animal models of diabetes. These models have been generated by pharmacological induction, feeding a galactose diet, and spontaneously by selective inbreeding or genetic modification. Among the available animal models, rodents have been studied most extensively owing to their short generation time and the inherited hyperglycemia and/or obesity that affect certain strains. In particular, mice have proven useful for studying DR and evaluating novel therapies because of their amenability to genetic manipulation. Mouse models suitable for replicating the early, non-proliferative stages of the retinopathy have been characterized, but no animal model has yet been found to demonstrate all of the vascular and neural complications that are associated with the advanced, proliferative stages of DR that occur in humans. In this review, we summarize commonly used animal models of DR, and briefly outline the in vivo imaging techniques used for characterization of DR in these models. Through highlighting the ocular pathological findings, clinical implications, advantages and disadvantages of these models, we provide essential information for planning experimental studies of DR that will lead to new strategies for its prevention and treatment.